2007
DOI: 10.17221/2234-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-stimulation on milk flow pattern and distribution of milk constituents at a quarter level

Abstract: Only the milk stored in the cisternal part of the udder is available for machine milking before milk ejection. Due to a high portion of milk stored in the alveolar part (more than 80%) the occurrence of milk ejection induced by tactile stimulation of the udder before milking is required for complete and fast milk removal. The normal milking liner pulsation also induces the milk ejection reflex during milking. However, the full milking vacuum after the removal of cisternal milk and before milk ejection causes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
(14 reference statements)
2
23
0
1
Order By: Relevance
“…This increase has been reported in many studies (Ontsouka et al, 2003;Bruckmaier et al, 2004;Sarikaya et al, 2005;Tan in et al, 2007). It is likely that the fat droplets, which are delimited by lipoprotein membranes, are held back by capillary forces in the alveoli and through adhesive forces on the udder epithelium during the process of milking.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…This increase has been reported in many studies (Ontsouka et al, 2003;Bruckmaier et al, 2004;Sarikaya et al, 2005;Tan in et al, 2007). It is likely that the fat droplets, which are delimited by lipoprotein membranes, are held back by capillary forces in the alveoli and through adhesive forces on the udder epithelium during the process of milking.…”
supporting
confidence: 61%
“…Hostetler et al (2003) showed that a hand-stripped post-milking-machine sample of colostrum exhibited lower IgG concentration (P < 0.05) than a hand premilking sample (10 mL) as well as the remaining milking machine fraction. Studies of colostrum fractionation from d 2 (Ontsouka et al, 2003) and of mature milk (Ontsouka et al, 2003;Bruckmaier et al, 2004;Sarikaya et al, 2005;Tan in et al, 2007) found that milk composition changes during the course of milking, which corresponds to a continuous character of milk ejection during milk removal (Bruckmaier et al, 1994;Bruckmaier and Blum, 1998). Thus, the concept that colostrum composition could also be different during the first milking remained unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sandrucci et al (2007) described a short tAN (0.89±0.47 min) that showed a wide variability similar to the present results for cows milked conventionally. Pre-stimulation positively influences the parameters of milk flow and therefore the efficiency of milk removal (Tančin et al 2007a). The tPL detected by Zucali et al (2009) was on average 2.8±1.7 min and decrease phase (tAB) showed an excessive duration of 2.5±1.3 min, which was in line with results detected by Sandrucci et al (2007).…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, the milk ejection is delayed and reduced the milk flow. This leads to bimodal milk flow curves (Tancin et al, 2007). In primiparous cows, manual stimulation may fail to induce milk ejection and milk ejection is disturbed for several weeks immediately after parturition, if the animals do not adapt to the machine milking (Bruckmaier et al, 1992;.…”
Section: Inhibition Of Milk Ejection Reflex During Milking In Camelmentioning
confidence: 99%